Does institution type affect access to finance for cassava actors in Nigeria? - Okoruwa, V.O.; Abass, A.; Akin-Olagunju, O.A.; Akinola, N.A. (Elsevier, 2020)
The cassava system in Nigeria is developing, with increasing attention to its potential positive outcomes. However, credit access is a major problem in expanding productive activities of the different actors across the value chains of cassava products. This study investigates the extent of access to credit by cassava actors with respect to the different financial institutions in the country using data obtained from a sample of 168 actors, including producers, processors, marketers, fabricators and end users. The study found that commercial banks had the highest disbursement rate (88.0%) despite higher interest rate charged, while government banks had the least (73.6%). Processors (79.5%) and marketers (79.4%) had highest credit access rate while fabricators (67.5%) had the least. Regression results revealed that cassava actors that patronized commercial banks particularly those who are medium scale had access to higher amount of credit. However, female actors and those using cooperative banks secured lower credit amount. In line with the results, Nigeria should champion private-sector-led credit provision through appropriate policies aimed at improving the capacity of the institutions. Financial institutions should be strengthened for better credit access by the cassava actors, and hence improve their productivity.